Corpos, enredos e perspectivas queers: olhares sobre as relações de gênero nas obras de Marcus Vinícius - Marotto, Rafael Gonçalves (2024)
The text presented here proposes an investigation of the body and plots present in the performances of Marcus Vinícius (1985-2012) constructed between the years 2007 and 2008, seeking to identify in his records and process files the narrative of his creation linked to a perspective strange. The study and analysis have their theoretical-methodological approach to the aesthetics of gender and sexuality of the counterculture, associated with Genetic Criticism and studies of Marcus Vinícius' creative archives. With the analysis, we seek to highlight how archives can reveal the mechanisms of their artistic production and their conceptions of art in the Espírito Santo scenario, linked to a brief history of queer themes in works built on Espírito Santo soil. With a methodological approach in Louro (2022), Butler (2010, 2023) and Salles (1992, 2013). It is proposed to understand the nomenclature that will be posted in parallel with MV's artistic works, as well as the reading of his production and interpretation of his recording materials. It is concluded, therefore, that Marcus Vinícius was an innovative and brilliant mind in the performative construction of his time, in addition to praising that the state of Espírito Santo has artistic works that generate possibilities for queer analyses, and even though he is often not mentioned , due to the heteronormative-patriarchal pattern, readings about the fruits of Marcus Vinícius, in some way, prove the opposite.